3
$\begingroup$

How to solve $\log_{4}(\sqrt{x^{4/3}})+3\log_{x}(16x)=7?$

I've tried everything from brute force to doing base change but nothing works. I was wondering what was the best way in solving this?

$\endgroup$
1
$\begingroup$

Consider changing the logarithmic base to a natural log, ie $$\log_{b}(x) = \frac{\ln(x)}{\ln(b)}$$ which then leads to \begin{align} \log_{4}(x^{2/3}) + 3 \, \log_{x}(16 \, x) &= 7 \\ \frac{\ln(x)}{3 \, \ln(2)} + \frac{3 \, \ln(16 \, x)}{\ln(x)} &= 7 \\ \frac{\ln(x)}{3 \, \ln(2)} + \frac{12 \, \ln(2) + 3 \, \ln(x)}{\ln(x)} &= 7 \\ \ln^{2}(x) - 12 \, \ln(2) \, \ln(x) + 36 \, \ln^{2}(2) &= 0 \\ \left(\ln(x) - 6 \, \ln(2) \right)^2 &= 0 \end{align} for which it is obtained $\ln(x) = 6 \, \ln(2) = \ln(2^{6})$ or $x = 2^{6} = 64$.

$\endgroup$
1
$\begingroup$

\begin{align} \log_{4}(\sqrt{x^{4/3}})+3\log_{x}(16x)&=7\\ \left(\frac{1}{2}\right)\left(\frac{4}{3}\right)\log_{4}(x)+3\log_{x}(4^2)+3\log_{x}(x)&=7\\ \frac{2}{3}\log_{4}(x)+\frac{6}{\log_4x}+3&=7\\ (\log_4x)^2-6\log_4x+9&=0\\ \log_4x&=3\\ x&=64 \end{align}

$\endgroup$
  • $\begingroup$ I understand everything except on how $3log_{x}(4^2)$ became $\frac{6}{log_4x}$? $\endgroup$ – John Rawls Jun 15 '17 at 1:37
  • 1
    $\begingroup$ $3\log_x(4^2)=6\log_x4$. $\log_x4=\frac{\log_44}{\log_4x}=\frac{1}{\log_4x}$ by the change of base formula. $\endgroup$ – CY Aries Jun 15 '17 at 1:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.